Electrical Performance and Stability of Zinc Air Fuel Cell Using Cathode Material of MnO2 - Wongyao, Nutthapon; seki, Yuki; Takamura, Dan (Journal of Advanced Development in Engineering and Science, 2023)
In theoretical theory, zinc air fuel cell (ZAFC) provides the high energy per volume, and then, it is suitable for small power generation unit. For ZAFC application, this can be noted that before ZAFC is employed to operate in real situation for producing electrical power, it have to be proved the stability of power generation. With this important note, the stability of cell output current was focused. In this research, the cell parameter of cathode material of manganese dioxide mixed with carbon (MnO2/C) for the direct reaction of the oxygen reduction by using air was investigated. The results revealed that the increasing of cathode material of MnO2 from 0.5 mg/cm2 to 2.0 mg/cm2 , the electrical performance of cell power density increased with 4.8 times. This increment cause of cell performance was also interpreted on the cell impedance. It was replied that the more reduction of oxygen at cathode side was performed due to the decrement of charge transfer resistance. Moreover, with high loading of MnO2, the cell provided more stability to produce electricity.